Re‐engaging psychology for (more) human geographies of the future. Issue 1 (30th November 2022) - Bunnell, Tim; Ng, Huiying; Yeo, Si Jie Ivin
Abstract: Recent work in several fields of psychology has advanced understanding of how humans imaginatively construct, simulate and (pre‐)feel the future. These advances have not yet been substantively engaged in social and cultural geography. In this paper, we identify, review and begin to draw together scholarship in human geography and several subfields of psychology on the ways in which people imagine and navigate towards the future. The most influential existing work on the future in geography has concerned powerful institutional and discursive depictions of threatening times‐to‐come. In contrast, psychological and neuroscientific work on cognitive processes involved in prospection extends possibilities for a human geographical approach to the future considering how people relate to discursive imaginaries and spatial environments. Reinvigoration of the human geography‐psychology nexus can further critical understanding of the spatialities through which futures are imaginatively formed and felt by individuals, and are thereby brought into the realm of political and social possibility.